Pengaruh Pijat Bayi Terhadap Bounding Attachment Dan Durasi Menyusui Pada Bayi 0-6 Bulan Di Wilayah Kerja Puskesmas Payung Sekaki - Novi Elvina Sari; Wiwi Sartika; Nurmaliza Nurmaliza (LPPM Universitas Abdurrab, 2023)
ABSTRACT Background: factors causing failure of exclusive breastfeeding are influenced by age, education, parity, formula feeding, culture and knowledge about breast milk production. Breast milk production can be increased by Bounding Attachment and breastfeeding duration based on the results of research (Hafid et al., 2022). Objective: The purpose of this study was to determine the frequency distribution of Bounding Attachment and breastfeeding duration before the intervention and after the intervention. in infants 0-6 months. Methods: This research design is a quasy experiment with a one group pretest-posttest design. In this study, respondents were given a pretest before being given baby massage to determine Bounding Attachment and breastfeeding duration. Then a posttest was conducted by giving baby massage 2x/week to determine Bounding Attachment and breastfeeding duration. Statistical tests used are T-dependent test and Wilcoxon test. Results: In this study, the average frequency of Bounding Attachmentt before the intervention was 7.97 after the intervention was given 9.38. It can be concluded that the provision of baby massage has an effect on Bounding Attachmentt. and the average value of breastfeeding duration before the intervention was 13.94 minutes with a standard deviation of 4.111 and a standard error of 0.727 minutes after the intervention was 20.97 minutes with a standard deviation of 5.409 minutes with a standard error of 0.9. Keywords: Baby massage 1, Bounding attachment 2, breastfeeding duration 3